TANTANGAN NEGARA-BANGSA (NATION-STATE) DALAM MENGHADAPI FUNDAMENTALISME ISLAM - Mustaqim, Muhamad; Miftah, Muhammad (ADDIN, 2015)
THE CHALLENGE OF THE NATION-STATE IN FACING THE ISLAMICFUNDAMENTALISM. Lately the discourse made the Islamic State in all over the world strengthened, especially the countries of the Middle East which has Islamic base. The concept of the nation-state that exists today is regarded as one of the major threat to the existence of Islamic values in the world. Therefore, it is no wonder that there are some groups of Muslims fighting for accomplishing the khilafah state, which they consider to be one of the solutions to revive the Islamic past. This article breaks down the concepts and history of fundamentalist Islam and how the nation-state see the concept of Islamic khilafah which is the main goal of the Islamic fundamentalist movement.